Optimization of Sperm Cryopreservation Protocol for Mediterranean Brown Trout: A Comparative Study of Non-Permeating Cryoprotectants and Thawing Rates In Vitro and In Vivo - Giusy Rusco; Michele Di Iorio; Pier Paolo Gibertoni; Stefano Esposito; Maurizio Penserini; Alessandra Roncarati; Silvia Cerolini; Nicolaia Iaffaldano (Animals, 2019)
The aim of our study was to test the effects of different non-permeating cryoprotectants (NP-CPAs), namely low-density lipoproteins (LDLs), sucrose, and egg yolk, and thawing rates on the post-thaw semen quality and fertilizing ability of the native Mediterranean brown trout. Pooled semen samples were diluted 1:3 (v:v) with 2.5%, 5%, 10%, or 15% LDL; 0.05, 0.1, or 0.3 M sucrose; or 10% egg yolk. At the moment of analysis, semen was thawed at 30 °C/10 s or 10 °C/30 s. The post-thaw semen quality was evaluated, considering motility, the duration of motility, viability, and DNA integrity. Significantly higher values of motility and viability were obtained using egg yolk/10 °C for 30 s, across all treatments. However, LDL and sucrose concentrations affected sperm cryosurvival, showing the highest post-thaw sperm quality at 5% LDL and 0.1 M sucrose. Based on the in vitro data, egg yolk, 5% LDL, and 0.1 M sucrose thawed at 10 °C or 30 °C were tested for the in vivo trial. The highest fertilization and hatching rates were recorded using egg yolk/10 °C (p < 0.05). According to these in vitro and in vivo results, egg yolk emerged as the most suitable NP-CPA and 10 °C/30 s as the best thawing rate for the cryopreservation of this trout sperm, under our experimental conditions.